2006
DOI: 10.1007/s00232-006-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Inward Rectifier Potassium Channels in Cultured Human Pulmonary Smooth Muscle Cells: Evidence for a Major Role of Kir2.4 Subunits

Abstract: Strong inwardly rectifying K + (K IR ) channels that contribute to maintaining the resting membrane potential are encoded by the Kir2.0 family (Kir2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Moreover, K IR 2.1 appeared to be involved in the K + -mediated vasodilation in contrast to K IR 2.2 (Zaritsky et al 2000). However, apart from K IR 2.1, Tennant et al (2006) reported a predominant role for K IR 2.4 in cultured human pulmonary artery smooth muscle cells.…”
Section: Functional Expression Of K Ir 2xmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, K IR 2.1 appeared to be involved in the K + -mediated vasodilation in contrast to K IR 2.2 (Zaritsky et al 2000). However, apart from K IR 2.1, Tennant et al (2006) reported a predominant role for K IR 2.4 in cultured human pulmonary artery smooth muscle cells.…”
Section: Functional Expression Of K Ir 2xmentioning
confidence: 86%
“…2000). However, apart from K IR 2.1, Tennant et al. (2006) reported a predominant role for K IR 2.4 in cultured human pulmonary artery smooth muscle cells.…”
Section: Kir2x Expression Profilesmentioning
confidence: 89%
“…For the experiments, MSCs were grown in 96‐ or 6‐well culture plates or on glass coverslips (placed on the bottom of a well of a 6 well‐plates), stimulated or not (control) with diode laser (time 0, T0), and cultured in growth medium for 24, 48, and 72 h. During laser irradiation the cells were incubated in Red Phenol free medium (GIBCO™, Invitrogen). In some experiments MSCs were treated with 0.5 mM BaCl 2 for 24 h prior laser irradiation in order to inhibit Kir channels (Tennant et al, 2006; Ma et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of the Kir current was assessed in voltage‐clamp by recording the currents in response to voltage ramps ranging from −120 to 50 mV over a period of 0.5 sec, which were imposed every 1 min from a holding potential of −60 mV and digitized at a rate of 5 kHz; two runs repeated every 20 sec were averaged. First, we used the control physiological solution without Ba 2+ (control) to record any K + current (I K,DR and I Kir ) followed by Ba 2+ addition to block I Kir (Tennant et al, 2006; Ma et al, 2011). Finally, the average of two ramps elicited in the presence of Ba 2+ was subtracted from control currents to evaluate I Kir .…”
Section: Methodsmentioning
confidence: 99%
“…Potassium channels regulate the resting membrane potential of pulmonary artery smooth muscle cells. [31][32][33] Voltage-gated potassium channels are involved in the hypoxic pulmonary vasoconstrictive response, 34 while downregulation of K v channel expression in PASMCs of PAH patients promotes PASMC excitability and proliferation, and excessive pulmonary arterial vasoconstriction. 20,35,36 Potassium channel openers may provide therapeutic benefit by opposing such deleterious pulmonary arterial remodeling 37 ; recently, pharmacological KCNK3 activation by ONO-RS-082 (ONO) attenuated development of pulmonary hypertension in a monocrotalineinduced rat model.…”
Section: Mutant and Wt Kcnk3 Channels Are Pharmacological Targets In mentioning
confidence: 99%